الألعاب الالكترونية في مؤسسات الشباب - باللموشي, عبد الرزاق; ضيف, حسين (جامعة الوادي - University of Eloued, 2019)
إلا أنه نظرا للتقدم الهائل في مجال الاعلام والاتصال وفي مجال البرمجيات نلاحظ أن الأطفال لم يعد تريقهم وتمتعهم الألعاب التقليدية التي نشأ وتربى من خلالها آباءهم وأمهاتهم والتي تمثل موروثا شعبيا بالنسبة للمجتمعات والتي بالإضافة لدورها في تفريغ طاقاتهم الزائدة وملأ أوقات فراغهم كانت تؤدي دورا تربويا وغرس قيم المجتمع وتأهيلهم الى الأدوار الاجتماعية المستقبلية ،بل نجد الألعاب الإلكترونية هي التي أصبحت تمتع وتجذب الأطفال بصورة رهيبة الى حد أنهم أصبحوا يفضلونها ويقضون فيها الوقت الطويل ولو على حساب ساعات تعلمهم بل حتى على حساب حاجاتهم الأساسية كالأكل والشرب والنوم . ولهذا وجب على كل مؤسسات التنشئة الاجتماعية أن تدق جرس الانذار وتلعب دورها في توجيه الطفل والمراهق نحو الاستخدام الأمثل لهاته الألعاب ومراقبتها . ومن بين هاته المؤسسات نجد المؤسسات الشبانية بمختلف أنواعها لها دور كبير في هذا المجال. فما هي الألعاب الإلكترونية؟ وما هي إيجابياتها؟ وماهي سلبياتها ؟ وما هي هاته المؤسسات ؟ وما أهميتها؟ وما دورها أتجاه الاستخدام المفرط للأطفال للألعاب الالكترونية ؟However, due to the tremendous progress in the field of media, communication and in the field of software, we notice that children no longer enjoy and enjoy the traditional games through which their parents were raised and raised, which represent a popular legacy for societies and which in addition to its role in emptying their extra energies and filling their spare time was playing an educational role. Inculcating community values and qualifying them for future social roles, we find electronic games that have become terribly enjoyable and attractive to children to the extent that they prefer them and spend a long time in them, even at the expense of their learning hours, even at the expense of their basic needs such as eating, drinking and sleeping . That is why all social upbringing institutions must ring the alarm and play their role in guiding the child and adolescent towards the optimal use of these games and monitoring them . Among these institutions, we find youth institutions of all kinds that play a major role in this field . So what are electronic games? What are its advantages? What are its disadvantages? What are these institutions? What is its importance? What is its role towards children's excessive
مقال
Keywords: الألعاب الالكترونية، مؤسسات الشباب; Electronic games, youth organizations